Theoretical studies of tournaments and the venture capital industry - Fang, D (2013)
This thesis consists of three essays. In essay 1, we examine the optimal contract design in the venture capital (VC) industry when a general partner (GP) cannot commit to putting effort into an existing partnership. We show that the first-best contract, a layered debt issued to investors, induces the GP's efficient investment decision and prevents him from diverting effort from the partnership, but its feasibility depends on economic conditions and on whether the GP's ability is observed. The model suggests a procyclical pattern of investment funding and a countercyclical pattern of industrial performance. Moreover, new GPs' fundraising and performance are more sensitive to business cycles than those of established ones. In essay 2, we study investment duration of a VC fund based on a simple agency conflict between a GP and investors. A short duration financing arrangement can minimize agency conflicts but may offer investors rents. When the rents offered to investors are too large, which may occur when the rate of return of a successful investment is high, the GP has an incentive to use less efficient but rent-saving financing arrangements. We show that there can be cases in which the GP uses a long investment duration financing arrangement or is willing to have the fund capital-constrained. In essay 3, we study contests where, subject only to a capacity constraint on mean performance, contestants, facing a rank-dependent payoff function, choose arbitrary performance distributions. In the case of symmetric capacity, we derive closed-form solutions for equilibrium performance distributions and analyze the effect of contest structure on equilibrium behavior. We show that equilibrium performance distributions are never dispersion-maximizing and are always right-skewed when the contest is selective. When contestants' capacities are private information, contests serve as a selection mechanism. We analyze the effect of changing contest parameters on strategies, payoffs, and contest selection efficiency and study the selection properties of different contest designs.